Acupuncture for refractory gastro-oesophageal reflux disease: a systematic review and meta-analysis protocol. Issue 8 (26th August 2019) - Li, Dacheng; Zhu, Li; Liu, Daming
Abstract : Introduction: Refractory gastro-oesophageal reflux disease (rGORD) is a common disease, affecting patients' quality of life. Since conventional medicines have limitations, like low effective rates and adverse events, acupuncture may be a promising therapy for rGORD. While no related systematic review has been published, the present study is designed to evaluate the efficacy and safety of acupuncture for rGORD. Methods and analysis: PubMed, the Cochrane Central Register of Controlled Trials and Chinese electronic databases, including China National Knowledge Infrastructure, Wan Fang database, VIP, SinoMed and the Chinese Clinical Trial Registry, will be searched from establishment of the database to 31 August 2019. There will be no limitations on language, and all articles will be screened and collected by two reviewers independently. RevMan V.5.3.5 software will be used for meta-analysis, and the conduction of study will refer to the Cochrane Handbook for Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocol guidelines. The efficacy and safety of acupuncture for rGORD will be evaluated based on outcomes, including global symptom improvement, oesophageal sphincter function test measured by high-resolution manometry, quality of life, recurrence rate and adverse events. Ethics and dissemination: There is no necessity for this study to acquire an ethical approval, and this review will be disseminated in a peer-reviewed journal or conference presentation. Trial registration number: CRD42018111912.